2-[2-(Trimethylsilyl)ethyl]isoindoline-1,3-dione - Guzei, Ilia A. (International Union of Crystallography, 2009)
In the course of our studies of silicon-containing anticancer compounds, the title compound, C(13)H(17)NO(2)Si, was synthesized. The geometrical parameters including the geometry about the Si atom are typical. The molecules form dimers via a weak C—H⋯O interaction described by the graph set R (2) (2)(10). The dimers are assembled in rows stacked in the crystallographic b-axis direction via π–π interactions with a 3.332 (3) Å separation between the rows.